ANALISA TINDAK PIDANA PEMBUNUHAN BAYI (INFANTICIDE) DI WILAYAH HUKUM PENGADILAN NEGERI SLEMAN - Isnawan, Fuadi (Jurnal Yuridis, 2018)
The infanticide crime is a special crime, in which one can do so is the biological mother of the infant. This specificity will be the core of this paper, reviewing the factors that cause the crime is done because it becomes the specificity of this criminal act. In addition to reviewing it, the writing of this paper will also be mebahasa about things that the judges consideration who hear cases of infanticide murder, whether in the form of a mitigating or incriminating reason. This research is conducted by empirical juridical who examine the crime according to reality in real life of society. The end of this study concluded that the main thing that causes a mother to kill her baby is the embarrassment factor, because it has given birth to a child outside a legal marriage.